0186 Sleep Quality and Expectations About Sleep are Associated with Performance in Individual Sports. (27th May 2020) - Carmichael, K E; O'Connor, P
Abstract: Introduction: Epidemiological studies on predictors of sport performance are rare. Some athletes report poor sleep the night prior to competition which may influence performance. The purpose of this study was to examine relationships between sleep and athletic performance in a sample of U.S. adults. Methods: Self-identified athletes (n=635), recruited from Amazon's Mechanical Turk website, completed demographic, sleep, and athletic performance questions. Participants were at least 18 years old and competed in at least one athletic competition during the prior 6 months. Sleep quality and perceived performance were rated on 5-point Likert scales (e.g., 1=sleep quality/performance was very much worse than usual to 5=very much better than usual). Additional questions asked about plausible confounding variables, including the presence of bodily pain, expectations about whether sleep influences sport performance, and intensity of effort given during the competition compared to usual effort. Results: The sample was 42% female and 71% Caucasian with 94% between the ages of 18 and 39 years; 358 (56.4%) participated in an individual sport and 277 (43.6%) were team sport athletes. The most common sports were running (35%), basketball (14%), and soccer (6%). For individual sport athletes, three variables predicted a significant amount of the variance in perceived performance (R 2 = 0.32, F(3, 354) = 56.30, p < .001): intensity of effort (β = 0.44, p < 0.001), sleep quality the night prior to competition (β = 0.14, p < 0.01), and expectations for performance change following a good night's sleep (β = 0.14, p < 0.01). Team sport athletes' perceived performance was predicted by the intensity of effort (β = 0.46, p < 0.001) and percentage of time spent in competition (β = 0.14, p = 0.01; R 2 = 0.26, F(2, 271) = 47.50, p < .001). Conclusion: Among individual sport athletes, and after adjusting for the intensity of their effort, prior night sleep quality and expectations regarding sleep and performance aided in predicting perceived performance. These relationships did not exist among team sport athletes, perhaps because of the greater error in estimating performance during team sport competition. Support: